Exchange-traded funds and the future of passive investments: a bibliometric review and future research agenda - Girish Joshi; Ranjan Kumar Dash (Future Business Journal)
Abstract Passive investments such as exchange-traded funds (ETFs) provide an opportunity to invest in indexes, asset classes, and sectors with low maintenance costs and high transparency. Today ETFs dominate the world, with nearly 50% of the investment in the USA coming through ETFs. Numerous studies on specific aspects on ETFs have been done earlier; however, considering the scarcity of thorough summaries in the existing body of literature, this bibliometric and systematic review aims to adopt a methodical approach with the goal of delivering qualitative and quantitative understanding of ETFs, while highlighting general research trends. The authors analyzed 2058 articles associated with ETFs from the Scopus database during the last 50 years, i.e., from 1973 till date. The search was initially conducted using title, keyword, and abstract, yielding 2058 articles, which were narrowed to only include research papers and review papers, resulting in a final count of 958 items. The most important authors, highest cited articles, prominent journals, important themes, and associated countries have been identified using bibliometric research. The numerical and visual representations of the analysis show that ETFs are a widely studied research area, and the enormous rise in publications in 2020, 2021, and 2022 demonstrates that researchers are quite interested in the topic. According to affiliation statistics, most research is focused in the USA together with other developed nations, opening new options for the research on ETFs in relation to developing economies. The current analysis reconciles numerous exchange-traded fund studies associated with volatility, liquidity, risk-return trade-off, and tracking errors and identifies possible research gaps. Some of the emerging topics that evolved in passive investments include the use of machine learning, AI, and the emergence of ETFs associated with ESG and sustainability. This research will help lawmakers, scholars, and regulators understand the core principles of ETFs and identify areas that deserve additional investigation.